Oxidative stress and biochemical markers in prenatally androgenized sheep after neonatal treatment with GnRH agonist - Nóbrega JE; Tonelotto dos Santos J; Serrano-Mujica LK; Bochi G; Moresco RN; Rissi VB; Glanzner WG; Langer FW; Antoniazzi AQ; Gonçalves PBD; Premaor MO; Comim FV (Dove Medical Press, 2019)
Jandui Escariãoda Nóbrega,1 Joabel Tonelotto dos Santos,1 Lady K Serrano-Mujica,1 Guilherme Bochi,2 Rafael Noal Moresco,2 Vitor Braga Rissi,1 Werner Giehl Glanzner,1 Felipe W Langer,3 Alfredo Quites Antoniazzi,1 Paulo Bayard Dias Gonçalves,1 Melissa O Premaor,3 Fabio V Comim1,3 1Laboratory of Biotechnology and Animal Reproduction – BioRep, Federal University of Santa Maria (UFSM), Santa Maria, RS, Brazil; 2Laboratory of Clinical Biochemistry, Department of Clinical and Toxicological Analysis, Federal University of Santa Maria (UFSM), Santa Maria, RS, Brazil; 3Department of Clinical Medicine, Federal University of Santa Maria (UFSM), Santa Maria, RS, Brazil Background: Disruption of the balance between the production of ROS and their removal through enzymatic and non-enzymatic (antioxidant) processes has been proposed as a new mechanism in the pathology of polycystic ovary syndrome (PCOS). Evidence from animal models of PCOS (prenatally androgenized sheep) has suggested that treatment with insulin sensitizers, but not antiandrogens, can reduce increases in ROS.Materials and methods: In the present study, we investigated the effects of neonatal treatment with a gonadotropin-releasing hormone (GnRH) agonist (leuprolide acetate) on prenatally androgenized sheep with testosterone propionate to determine its impact on oxidative stress molecules (ferric reducing antioxidant power [FRAP], advanced oxidation protein product [AOPP], nitric oxide [NOx], albumin) at 8, 12, and 18 months of age.Results: Androgenized ewes (but not leuprolide-treated ewes) showed reduced total cholesterol levels associated with a decrease in the ratio of visceral to subcutaneous adiposity (adjusted to abdominal area) as determined by computed tomography. In androgenized ewes at 12 months of age, an increase in subcutaneous fat and relative decrease in the visceral fat compartment did not affect the expression of REDOX markers. At 18 months of age, however, the levels of NOx metabolites decreased in androgenized animals, but remained close to normal in ewes subjected to neonatal treatment with leuprolide acetate. Other oxidative stress parameters (FRAP, AOPP, albumin) did not vary among groups.Conclusion: Our results demonstrate that the GnRH agonist leuprolide (as a single dose after birth) had weak effects on markers of the oxidative stress balance. Keywords: animal model of polycystic ovary syndrome, oxidative stress, gonadotropin-releasing hormone agonist, sheep, metabolism